Magnetism in Lithium–Oxygen Discharge Product. Issue 7 (13th May 2013) - Lu, Jun; Jung, Hun‐Ji; Lau, Kah Chun; Zhang, Zhengcheng; Schlueter, John A.; Du, Peng; Assary, Rajeev S.; Greeley, Jeffrey; Ferguson, Glen A.; Wang, Hsien‐Hau; Hassoun, Jusef; Iddir, Hakim; et al.
Abstract Nonaqueous lithium–oxygen batteries have a much superior theoretical gravimetric energy density compared to conventional lithium‐ion batteries, and thus could render long‐range electric vehicles a reality. A molecular‐level understanding of the reversible formation of lithium peroxide in these batteries, the properties of major/minor discharge products, and the stability of the nonaqueous electrolytes is required to achieve successful lithium–oxygen batteries. We demonstrate that the major discharge product formed in the lithium–oxygen cell, lithium peroxide, exhibits a magnetic moment. These results are based on dc‐magnetization measurements and a lithium–oxygen cell containing an ether‐based electrolyte. The results are unexpected because bulk lithium peroxide has a significant band gap. Density functional calculations predict that superoxide‐type surface oxygen groups with unpaired electrons exist on stoichiometric lithium peroxide crystalline surfaces and on nanoparticle surfaces; these computational results are consistent with the magnetic measurement of the discharged lithium peroxide product as well as EPR measurements on commercial lithium peroxide. The presence of superoxide‐type surface oxygen groups with spin can play a role in the reversible formation and decomposition of lithium peroxide as well as the reversible formation and decomposition of electrolyte molecules.